Deliberate self-harm in adolescents in Oxford, 1985-1995. - Hawton, K; Fagg, J; Simkin, S; Bale, E; Bond, A (2000)
Deliberate self-harm (DSH) has been one of the major health problems of adolescents in the U.K. for many years. Any changes in rates of DSH or the demographic characteristics of the patient population are likely to have important implications for clinical services and for future suicidal behaviour. Following a decline in rates in the late 1970s and mid 1980s, there were signs in the late 1980s that rates were beginning to increase again. We have used data collected by the Oxford Monitoring System for Attempted Suicide on the basis of patients presenting to the general hospital in Oxford to review trends in DSH in under 20-year-olds between 1985 and 1995. There was a substantial increase in the numbers of teenage DSH patients during the 11-year study period, with an increase between 1985-1986 and 1994-1995 of 27.7% in males, 28.3% in females, and 28.1% overall. There were no demographic changes within the catchment area to explain a change of this size. As rates of repetition of DSH also increased in both sexes during the study period the overall number of episodes of DSH rose even more between 1985-1986 and 1994-1995 (+56.9% in males, +46.3% in females, and +49.4% overall). As in previous studies the majority of adolescents had interpersonal problems and/or difficulties with studying or employment. Self-poisoning with paracetamol and paracetamol compounds became increasingly common such that by 1995 these were used in almost two-thirds of overdoses. The recent increase in DSH in adolescents has important implications for general hospital and adolescent psychiatric services. The greater frequency of repetition of DSH may herald increased future suicide rates. The case for restricting the amount of paracetamol available is overwhelming. Evaluative trials of specific interventions following adolescent DSH are urgently required.